A centralidade da Aldeota como expressão da dinâmica intra-urbana de Fortaleza - Diogenes, Beatriz Helena Nogueira (2005)
The neighborhood of Aldeota, a residential area of the wealthy class of Fortaleza, has become in recent decades an area of ​​centrality of significant relevance in the metropolis of Fortaleza. Changes in the way of using and occupying space, with the emergence of new functions, in addition to changes in the way of inhabiting, lead to an intense change in the physiognomy of the neighborhood. The main objective of the research is to study the constitution and consolidation of this centrality, involving the factors that contribute to its formation. It intends to examine and analyze the relevant transformations that have taken place in the structuring of the urban space of the neighborhood, in a research exercise on the intra-urban dynamics of Fortaleza. In this sense, the work seeks to identify the main factors that led to the emergence of this new center in the metropolis, taking into account the initial situation of the neighborhood as a high-income residential area. It deals, therefore, with historical aspects related to its emergence and evolution since the early decades of the 20th century, as well as its consolidation as an elegant neighborhood in the city of Fortaleza, until the mid-1970s. Then, it analyzes the process of development of the neighborhood , when it became a vertical residential area and location of commerce and services offered to a wealthy elite, from that period to the present day. At the same time, the study seeks to investigate the forms of interrelation between this center and the general growth of the metropolis, with the aim of understanding and ascertaining the changes brought about in the internal dynamics of Fortaleza. The work also analyzes the question of the centrality of the Aldeota based on the theoretical references investigated, in order to understand and conceptualize the nature of the centrality developed in the neighborhood, seen as a significant and differentiated space in the context of the City, with its own characteristics, acquiring form particular development and expansion. The centrality formed in the Aldeota neighborhood constitutes an urban issue of current relevance, mainly because it translates the specificities of the urban production process that took place in the metropolis of Fortaleza.